2012
DOI: 10.3141/2300-15
|View full text |Cite
|
Sign up to set email alerts
|

Trade Space Analysis of Surface Alternatives for Short-Haul Passenger Air Travel

Abstract: Intercity passenger transportation is a time- and energy-intensive activity. Despite a growing social consciousness of “green” alternatives, travelers continue to choose routes and modes primarily on the basis of travel time and cost. Although long-distance trips of more than 500 mi (800 km) are dominated by air travel, short- and medium-haul trips compete with surface modes when total travel time and cost are compared. Because of hub-and-spoke air transport networks, short-haul air travel is bundled with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Some benefits to travelers were mentioned earlier, such as reduced congestion, increased choices, and improved reliability; others include potentially increased convenience and comfort (e.g., a trip by train rather than by a narrow-body plane) or better access (e.g., a long-distance bus service directly to an airport rather than first transferring to a city center station). Even without including the preferential city access that ground modes can provide versus flights, Audenaerd et al found that total travel, transfer, and terminal processing time can be reduced for passengers making short-haul trips to and from Chicago O'Hare International Airport by ground rather than by air (12).…”
Section: Traveler and Operator Benefitsmentioning
confidence: 99%
“…Some benefits to travelers were mentioned earlier, such as reduced congestion, increased choices, and improved reliability; others include potentially increased convenience and comfort (e.g., a trip by train rather than by a narrow-body plane) or better access (e.g., a long-distance bus service directly to an airport rather than first transferring to a city center station). Even without including the preferential city access that ground modes can provide versus flights, Audenaerd et al found that total travel, transfer, and terminal processing time can be reduced for passengers making short-haul trips to and from Chicago O'Hare International Airport by ground rather than by air (12).…”
Section: Traveler and Operator Benefitsmentioning
confidence: 99%